Promoting human capital through social entrepreneurship: a comparative study of Indonesia and China - Ramlee Mustapha; Veronica Zapata; Julie Jung-Kim (penerbit ukm, 2008)
The hybrid model of social and profit-making enterprise has been the hallmark of social entrepreneurship. Yet, unlike the conventional entrepreneurs, social entrepreneurs seek to alter the “status quo” of mainly rural, marginalized, disadvantaged and poor citizens. Due to their relatively large proportion of rural population, Indonesia and China were selected as case studies. Even though Indonesian and Chinese social entrepreneurial activities have increased over the years and their share in economic output has been significant, their overall development and growth are encumbered by numerous barriers. Thus, it is critical to examine the supportive and suppressive factors of social entrepreneurship in these two major Asian countries. Specifically, this article focuses on social, political, cultural and economic intricacies and their implications on social entrepreneurship. This article reviews several case studies and uses secondary data to make comparison based on the theory of social entrepreneurship put forward by Dees (2001). The similarities between Indonesia and China in terms of social entrepreneurship are as follows: (a) the limited success of social entrepreneurship, (b) the prevalence of governmentcontrol over micro-economic activities, (c) strong bureaucratic red tape, (d)lack of education and training, and (e) lack of resources. However, there are unique differences between Indonesia and China. Social entrepreneurs in Indonesia focused on micro-enterprises in the non-formal sector and microfinance; whereas social entrepreneurs in China put emphasis on social efficiency, autonomy and the search for better modus operandi.